2021
DOI: 10.1016/j.stemcr.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

A Scalable Suspension Platform for Generating High-Density Cultures of Universal Red Blood Cells from Human Induced Pluripotent Stem Cells

Abstract: Summary Universal red blood cells (RBCs) differentiated from O-negative human induced pluripotent stem cells (hiPSCs) could find applications in transfusion medicine. Given that each transfusion unit of blood requires 2 trillion RBCs, efficient bioprocesses need to be developed for large-scale in vitro generation of RBCs. We have developed a scalable suspension agitation culture platform for differentiating hiPSC-microcarrier aggregates into functional RBCs and have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 44 publications
2
66
2
Order By: Relevance
“…Recently, Sivalingam et al established a protocol for scalable differentiation for hiPSC-microcarrier aggregates in 500 mL spinner flasks, with about a 1000-fold expansion of the functional erythroblasts (see Table 1 ). Whilst hiPSC-derived erythroblasts exhibit low enucleation (6%), a co-culture with OP9 on the microcarriers resulted in up to 59.3% enucleation in vitro [ 72 ].…”
Section: Cell Sources For In Vitro Erythropoiesismentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Sivalingam et al established a protocol for scalable differentiation for hiPSC-microcarrier aggregates in 500 mL spinner flasks, with about a 1000-fold expansion of the functional erythroblasts (see Table 1 ). Whilst hiPSC-derived erythroblasts exhibit low enucleation (6%), a co-culture with OP9 on the microcarriers resulted in up to 59.3% enucleation in vitro [ 72 ].…”
Section: Cell Sources For In Vitro Erythropoiesismentioning
confidence: 99%
“…Additionally, the co-culture condition yielded a higher frequency of late-stage erythroblasts and even some levels of enucleation (see Table 1 ). Another mouse bone marrow stromal cell line, OP9, was able to reduce apoptosis of expanding iPSC-erythroblasts and improved enucleation by about three- to ten-fold [ 72 ]. More importantly, the authors also showed that OP9 can be grown on microcarriers (microbeads that greatly improve the growth area of adherent cells in a suspension culture) and thus demonstrating the scalability of their iPSC-erythrocyte platform.…”
Section: Approaches To Enhance Erythroid Differentiation From Hipscsmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes roller bottles (Y. Zhang et al, 2017), rocking motion bioreactors (Boehm et al, 2010; Timmins et al, 2011), shake flasks (Aglialoro et al, 2021; Sivalingam et al, 2020), and spinner flasks (Griffiths et al, 2012; Kupzig et al, 2017; Sivalingam et al, 2020; Trakarnsanga et al, 2017). Stirred tank reactors (STRs) additionally allow for online monitoring and control of process parameters such as pH, dissolved oxygen and nutrient concentrations.…”
Section: Introductionmentioning
confidence: 99%